FINANCIAL SUPPORT OF AGRICULTURAL ENTERPRISES - Levandivskyi , O.T.; Drebot, S.D. (The actual problems of regional economy development, 2019)
The purpose of the article is to determine the role of bank lending in the financial support of agricultural enterprises, to analyze the factors that impede the development of credit relations, to work out directions of stabilization of the mechanism of lending to agricultural enterprises in Ukraine. The article explores approaches to the study of financial support of agricultural enterprises in modern conditions of management. The genesis of this problem shows the main approaches. It is emphasized that modern agriculture is closely linked to financial and credit institutions. The individual directions of financial support are substantiated. At the same time, it is considered that lending to agricultural enterprises is an important tool for sustainable development of the state and ensuring its food security. However, in the current context, the issue of financial support of the agricultural sector requires a new approach, improvement of the considered state support programs through active measures at the level of agricultural enterprises, introduction of new financial and credit structures. It is emphasized that the organization and management of agricultural production, as well as the development of measures to improve its organizational and economic mechanism must be taken into account, the features of agricultural activities without which it is impossible to achieve a high level of production efficiency.